2019
DOI: 10.1021/acs.chemmater.9b02987
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Insights into the Rapid, Light-Induced Auto-Oxidation of Molybdenum Disulfide Aqueous Dispersions

Abstract: The production of exfoliated MoS2 via lithium intercalation has been widely used to prepare 1T polytype dominated MoS2 (1T-MoS2) monolayers. These metallic single layers hold promise as high-performance electrodes for various electrochemical applications as well as for direct conversion to the semiconducting 2H polytype (2H-MoS2), a material of significant interest for next-generation electronics and optoelectronics. The performance in these applications is largely determined by defects introduced during proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The XPS results also indicate the presence of MoO 2 and MoO 3 which comprise 5.72% of the bulk MoS 2 powder but are also formed during processing when the material is exposed to light and oxygen via a mechanism recently reported by us . The untreated samples showed 22.4% MoO x content, which was reduced to 17.1% MoO x content following heat treatment at 150 °C and further reduced to 3.61% MoO x content at 300 °C.…”
Section: Results and Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The XPS results also indicate the presence of MoO 2 and MoO 3 which comprise 5.72% of the bulk MoS 2 powder but are also formed during processing when the material is exposed to light and oxygen via a mechanism recently reported by us . The untreated samples showed 22.4% MoO x content, which was reduced to 17.1% MoO x content following heat treatment at 150 °C and further reduced to 3.61% MoO x content at 300 °C.…”
Section: Results and Discussionsupporting
confidence: 61%
“…The XPS results also indicate the presence of MoO 2 and MoO 3 which comprise 5.72% of the bulk MoS 2 powder but are also formed during processing when the material is exposed to light and oxygen via a mechanism recently reported by us. 37 The untreated samples showed 22.4% MoO x content, which was reduced to 17.1% MoO x content following heat treatment at 150 °C and further reduced to 3.61% MoO x content at 300 °C. Acid flocculation was suspected to have caused the increase in MoO x content, which was verified through XPS of MoS 2 nanosheets before and after acid treatment and can be found in the Supporting Information (Figure S3).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to Michael et al , MoS 2 is more likely to be present in the form of MoO 4 2+ rather than MoO 3 when oxidized. 48 In the ex situ XPS, we can clearly see a peak of Mo at 235.5 eV, again proving that some MoS 2 was oxidized during the cycle. Curiously, in the ex situ XPS for the samples discharging to 0.9 V and 0.5 V and charging to 1.5 V, we can see a clear peak at 228.0 eV, showing the existence of Mo, which is not consistent with the previous paper.…”
Section: Resultsmentioning
confidence: 70%
“…The superior light-driven antibacterial activity of 1T-MoS 2 NFs compared to 2H-MoS 2 NFs may be due to phase differences between the metallic and semiconducting phases. Previous reports demonstrated that metallic 1T-MoS 2 NFs produce photoelectrons under light irradiation by a photoelectronic effect. The mechanism of the light-driven antibacterial activity of 1T-MoS 2 NFs appears to be that, with light irradiation, photoelectrons generated by metallic 1T-MoS 2 NFs further reacted with oxygen to generate superoxide ( • O 2 – ), as shown in Figure . Under light irradiation, the semiconducting 2H-MoS 2 NFs formed photoinduced electron–hole pairs.…”
Section: Resultsmentioning
confidence: 97%